Composition analysis of natural gas by combined benchtop NMR spectroscopy and mechanistical multivariate regression. (November 2022) - Duchowny, Anton; Mohnke, Oliver; Thern, Holger; Dupuy, Pablo Matias; Widerøe, Hege Christin; Faanes, Audun; Paulsen, Anfinn; Küppers, Markus; Blümich, Bernhard; Adams, Alina
Abstract: Natural gas is an essential energy source for a large variety of applications in today's society. Forecasts predict that it will also play a vital role in decarbonizing the energy sector. The price of natural gas is determined by its calorific value, which depends on its composition. Thus, the accurate composition quantification of natural gas is essential to both producers and consumers. In this context, proton Nuclear Magnetic Resonance (NMR) spectra of pure and mixed hydrocarbon gases have been studied with a desktop spectrometer in the range between 1 to 200 bar. Although spectral linewidth, chemical shift, and relaxation times depend on pressure and composition, the hydrocarbon concentrations of binary, ternary, and an eleven-component gas mixture could be quantified by spectral analysis using Spectral Hard Modeling, a mechanistical multivariate regression. Concentrations determined for the main components at 200 bar by NMR deviated by 0.1 to 0.18 mol% from Gas Chromatography values, leading to a difference in calorific values of only 0.15%. The presented results demonstrate that benchtop NMR combined with chemometrics can quantify complex hydrocarbon-gas mixtures reliably and quickly. Graphical abstract: Highlights: High-pressure setup for in situ benchtop NMR analysis up to 200 bar. Composition quantification and physical property assessment of complex gas mixtures. Mechanistical multivariate regression proved beneficial for spectral analysis. Accuracies are within industrial demands and partially abide official regulations.